Process and Practices of Community Participation in School Education of Nepal - Aryal, Shiva (Rupantaran: A Multidisciplinary Journal, 2021)
Formally, community participation in schools was started after the establishment of democracy. It has really a good influence on development of physical infrastructure and efficient use of local resources for school development. In this context, this article analyses the existing situation of level of participation and struggle of member of SMC experiences while they are working as authority’s persons. It is a drawing upon a grounded theory. The site and sample both are purposive and information was also collected by open-ended interview with real stakeholders. This article argues that poor language and economic status as well as lack of awareness of community people, political intervention and differences between home and school culture are subjected to what fairer terms of difficulty of community participation within schools for backward society with illustration how such problems influence on participatory decision making practice in school. This article emphasizes the need of education policy; it is obviously based on the society’s socio-economic and intellectual capacity.